Ethical Leadership Perceptions: Does It Matter If You’re Black or White? - Marquardt, Dennis J. (Journal of business ethics, 2018)
Ethical scandals in business are all too common. Due to the increased public awareness of the transgressions of business executives and the potential costs associated with these transgressions, ethical leadership is among the top qualities sought by organizations as they hire and promote managers. This search for ethical leaders intersects with a labor force that is becoming more racially diverse than ever before. In this paper, we propose that the ethical leadership qualities of business leaders may be perceived differently depending upon the race of the leader. Using two experimental studies in the USA, we examine the difference in ethical leadership perceptions between a Black (White) hypocritical CEO and an ethical CEO (Study 1). Next, we consider a Black (White) ethically ambiguous CEO and an ethical CEO (Study 2). The findings indicate that a Black leader faces larger negative impact in hypocritical and ambiguous conditions than a similar White leader. There were no significant race effects in the ethical conditions in which a leader demonstrated a personal commitment to ethics through words or actions. We discuss the implications of these findings.